PROFILE AND CONSISTENCY OF KERNEL QUALITY PT. DARIA DHARMA PRATAMA LUBUK BENTO PALM OIL PROCESSING INDUSTRY - Hasan Basri Daulay; Pandu Imam Sudibyo; Muhammad Hidayat Subha (BPFP Faperta UNIB, 2019)
Kernel quality is an important consideration in kernel marketing. The main kernel quality parameters are moisture content, impurities and broken core. The purpose of this study is to explain the profile and consistency of kernel quality at PT. Daria Dharma Pratama Lubuk Bento. The research method used was a survey by collecting data on monthly averages of moisture content, impurities and broken core during May 2017-April 2018; and the daily average of moisture content, impurities and broken core which are measured directly every day during May 2018; and interviews with several company officials to confirm the validity of the data that has been collected. Data analysis was performed by plotting each kernel quality parameter data both monthly and daily data that had been obtained on the abscissa-ordinate axis to be able to explain and compare it with SNI standards and company targets. Based on data analysis found that the moisture content of the PMKS kernel of PT. Daria Dharma Pratama Lubuk Bento generally meets SNI standards and also meets company targets; however the levels of impurities do not meet SNI standards even though they are in accordance with company targets; and the degree of rupture of the kernel does not meet SNI standards nor company targets. In general, the daily average moisture content, daily average impurities content and daily average damaged core content are highly volatile, which means that it is inconsistent; which is allegedly due to the high percentage of dura fruit that is generally from cultivated community plantations.Mutu kernel merupakan salah satu pertimbangan penting dalam pemasaran kernel. Parameter mutu kernel yang utama adalah kadar air, kadar kotoran dan inti pecah. Tujuan penelitian ini adalah untuk menjelaskan profil dan konsistensi mutu kernel di PT. Daria Dharma Pratama Lubuk Bento. Metode penelitian yang digunakan adalah survey dengan mengumpulkan data rata-rata bulanan kadar air, kadar kotoran dan kadar inti pecah selama Mei 2017- April 2018; dan rata-rata harian kadar air, kadar kotoran dan kadar inti pecah yang diukur langsung setiap hari selama Mei 2018; serta wawancara dengan beberapa petugas perusahaan untuk konfirmasi data sekender yang telah ditemukan. Analisis data dilakukan dengan cara memplotkan masing-masing data parameter mutu kernel baik data bulanan maupun harian yang telah didapat pada sumbu absis-ordinat untuk dapat menjelaskan dan membandingkannya dengan standar SNI dan target perusahaan. Berdasarkan analisis data didapatkan bahwa kadar air kernel PMKS PT. Daria Dharma Pratama Lubuk Bento pada umumnya telah memenuhi standar SNI dan juga memenuhi target perusahaan; akan tetapi kadar kotorannya tidak memenuhi standar SNI meskipun telah sesuai dengan target perusahaan; dan kadar kernel pecahnya tidak memenuhi standar SNI maupun target perusahaan. Secara umum, rata-rata harian kadar air, rata-rata harian kadar kotoran maupun rata-rata harian kadar inti rusak sangat fluktuatif yang berarti tidak konsisten; yang diduga karena tingginya persentase buah dura yang umumnya dari kebun masyarakat yang diolah